REVISITING GENDER TOUGHT IN ISLAMIC STUDIES - Khasanah, Karimatul (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2017)
Women issue viewed from religions perspective will be always interesting to study. It is because religion often does